2011
DOI: 10.1002/ccd.23010
|View full text |Cite
|
Sign up to set email alerts
|

Migrating type a intramural hematoma after repair of an anomalous right coronary artery aortocoronary dissection with a covered stent

Abstract: Iatrogenic aortocoronary dissection is a rare and potentially life-threatening complication of percutaneous coronary intervention (PCI). Prompt coronary stenting can stop progression and avoid the need for surgical intervention. Herein, we describe a case of migrating aortic intramural hematoma (IMH) after repair of an anomalous right coronary artery aortocoronary dissection with a covered stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…We adopt a conservative approach after an integration of clinical and different imaging modalities. Other studies have reported similar clinical behaviour 4 12. However, the unpredictable natural history of IMH with the possibility to develop complications even some months after the acute episode, independently from haematoma imaging characteristics, makes long-term surveillance necessary 13 14.…”
Section: Discussionmentioning
confidence: 89%
“…We adopt a conservative approach after an integration of clinical and different imaging modalities. Other studies have reported similar clinical behaviour 4 12. However, the unpredictable natural history of IMH with the possibility to develop complications even some months after the acute episode, independently from haematoma imaging characteristics, makes long-term surveillance necessary 13 14.…”
Section: Discussionmentioning
confidence: 89%